2016
DOI: 10.1108/ijbm-07-2015-0110
|View full text |Cite
|
Sign up to set email alerts
|

The role of customer brand engagement and brand experience in online banking

Abstract: Purpose The purpose of this paper is to examine the extent to which the customer-brand engagement influences the brand satisfaction and the brand loyalty in an online banking context. It further explores the role of the online brand experience as a mediating variable amidst the relationship of customer-brand engagement with brand satisfaction and brand loyalty. Design/methodology/approach This study has used 348 responses been collected through an online survey which was conducted among various online bank c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

11
150
0
4

Year Published

2018
2018
2023
2023

Publication Types

Select...
6
4

Relationship

0
10

Authors

Journals

citations
Cited by 150 publications
(165 citation statements)
references
References 68 publications
11
150
0
4
Order By: Relevance
“…In the B2B context, corporations are continuously under pressure to ensure that customers are satisfied and committed to use what the supplier offers and to strengthen the competitive position of a brand. Therefore, the antecedents of customer satisfaction have been wildly explored [85,86]. Moreover, scholars have also explored its consequences.…”
Section: Organizational Satisfaction and Customer Commitment In The Bmentioning
confidence: 99%
“…In the B2B context, corporations are continuously under pressure to ensure that customers are satisfied and committed to use what the supplier offers and to strengthen the competitive position of a brand. Therefore, the antecedents of customer satisfaction have been wildly explored [85,86]. Moreover, scholars have also explored its consequences.…”
Section: Organizational Satisfaction and Customer Commitment In The Bmentioning
confidence: 99%
“…Customer engagement (CE) is depicted as a way to create, build, and improve customer relationships (Abbas et al, 2018;Brodie et al, 2013) and is regarded as a strategic imperative to build a sustained competitive advantage (Hollebeek, 2012;Islam et al, 2019;Kumar & Pansari, 2016;Van Tonder & Petzer, 2018). Similarly, CE is a concept that is being examined as a tool to facilitate predictive power of customer behavior which includes loyalty and referrals (Brodie et al, 2011;Khan et al, 2016;Thakur, 2016;Zhang et al, 2017). The extant literature indicates that CE makes a strategic contribution to firms and have the potentiality to impact customer loyalty (Hollebeek, 2011a;Islam et al, 2019), firm reputation (Dijkmans et al, 2015), firm performance (Rather et al, 2019;So et al, 2014;Van Doorn et al, 2010), and firm value (Vivek et al, 2014;Zhang et al, 2017).…”
Section: Introductionmentioning
confidence: 99%
“…These studies indicate that satisfied customers repurchase offered products or services. To feel satisfied, customers must perceive a positive experience with the offered brand (Khan et al, 2016;Yulianti & Tung, 2013). These studies indicated that customer would be more satisfied toward a particular brand if they perceive a positive experience toward the brand.…”
Section: Introductionmentioning
confidence: 99%